Media Dan Bayang-Bayang Maqasid Al-Mukallaf (Trial By The Press Dan Pemberitaan) Studi Kasus Harian Berita Kota Kendari - Adi Ashadi L. Diab (Institut Agama Islam Negeri Kendari, 2018)
The article points out the news broadcasted by mass media influenced by maqashid al-mukallaf. It aims to create a harmony delivered to the society. This paper employs the theory of existence which includes several elements; such as frame, stereotype, prejudice, and the situation definition. This article indicates that based on the media perspective, the news coverage cannot be restricted by only certain authorized sides, but ethics and conscience. When certain journalists find and listen to certain statement, they are encouraged to select, write, and delete certain information before broadcasting it as the news. News may not harm anyone. There are three levels of benefit; trick cannot leave the benefits behind. Trick or manipulation is not allowed if it violates the benefits, therefore law manipulation is prohibited. Media will be punished after doing contempt of which means that media is considered doing trial by press and need to take its responsibility.